Not all therapeutic antibody isotypes are equal: the case of IgM versus IgG in Pertuzumab and Trastuzumab. Issue 10 (19th February 2020) - Samsudin, Firdaus; Yeo, Joshua Yi; Gan, Samuel Ken-En; Bond, Peter J.
Abstract : The IgM antibody isotype of Pertuzumab affords simultaneous binding to antigens, but similar binding in Trastuzumab is hindered by steric clashes. Abstract : The therapeutic potential of immunoglobulin M (IgM) is of considerable interest in immunotherapy due to its complement-activating and cell-agglutinating abilities. Pertuzumab and Trastuzumab are monoclonal antibodies used to treat human epidermal growth factor receptor 2 (HER2)-positive breast cancer but exhibit significantly different binding affinities as IgM when compared to its IgG isotype. Using integrative multiscale modelling and simulations of complete antibody assemblies, we show that Pertuzumab IgM is able to utilize all of its V-regions to bind multiple HER2 receptors simultaneously, while similar binding in Trastuzumab IgM is prohibited by steric clashes caused by the large globular domain of HER2. This is subsequently validated by confirming that Pertuzumab IgM inhibits proliferation in HER2 over-expressing live cells more effectively than its IgG counterpart and Trastuzumab IgM. Our study highlights the importance of understanding the molecular details of antibody–antigen interactions for the design and isotype selection of therapeutic antibodies.